Solve the equation (-2x-20)/3=y

\frac{-2x-20}{3}=y

Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Answer

$y=\frac{4}{3}x-\frac{20}{3}$

Step by step solution

Problem

$\frac{-2x-20}{3}=y$
1

Split the fraction $\frac{-2x+-20}{3}$ in two terms with same denominator

$\frac{-20}{3}+\frac{-2x}{3}=y$
2

Divide $-20$ by $3$

$\frac{-2x}{3}-\frac{20}{3}=y$
3

Apply the formula: $\frac{b\cdot a}{c}$$=b\frac{a}{c}$, where $a=-2$, $b=x$ and $c=3$

$-2\left(-\frac{2}{3}\right)x-\frac{20}{3}=y$
4

Multiply $-\frac{2}{3}$ times $-2$

$\frac{4}{3}x-\frac{20}{3}=y$
5

Grouping terms

$-y-\frac{20}{3}+\frac{4}{3}x=0$
6

Moving the term $-\frac{20}{3}$ to the other side of the equation with opposite sign

$\frac{4}{3}x-y=\frac{20}{3}$
7

Subtract $\frac{4}{3}x$ from both sides of the equation

$-y=\frac{20}{3}-\frac{4}{3}x$
8

Multiply both sides of the equation by $$

$y=-\left(\frac{20}{3}-\frac{4}{3}x\right)$
9

Multiply $\left(\frac{20}{3}+-\frac{4}{3}x\right)$ by $-1$

$y=\frac{4}{3}x-\frac{20}{3}$

Answer

$y=\frac{4}{3}x-\frac{20}{3}$

Problem Analysis

Main topic:

Polynomials

Time to solve it:

0.26 seconds

Views:

94